The association between episodes of night eating and levels of depression in the general population. Issue 2 (17th January 2022) - Kim, Woorim; Ju, Yeong Jun; Lee, Soon Young
Abstract: Objective: Research has suggested that a correlation may exist between depressive mood and episodes of night eating. This study aimed to examine whether having episodes of night eating was associated with increased levels of depression. Method: This study used data from the 2019 Korea Community Health Survey and the study population consisted of adults aged ≥19 years. Depression levels were measured using the Patient Health Questionnaire‐9. We investigated the patients' general characteristics using t ‐tests and analysis of variance. The association between depression levels and episodes of night eating was analyzed using a multivariable linear regression analysis. Subgroup analysis was conducted based on daily sleep duration. Results: We analyzed 34, 358 individuals and found higher average depression scores (β: 4.99, p  < .001) in those with episodes of night eating than those without. Large effect sizes were found for differences in depression scores between participants with and without episodes of night eating. The magnitude of this increase was particularly pronounced in individuals who reported 9 or more hours of sleep per day. Discussion: An association was found between levels of depression and episodes of night eating as individuals with episodes of night eating were more likely to have higher depression scores. Our findings suggest the potential need to consider night eating when addressing the mental health of the general population.